EGFR mutation correlates with uninflamed phenotype and weak immunogenicity, causing impaired response to PD-1 blockade in non-small cell lung cancer. (2nd November 2017) - Dong, Zhong-Yi; Zhang, Jia-Tao; Liu, Si-Yang; Su, Jian; Zhang, Chao; Xie, Zhi; Zhou, Qing; Tu, Hai-Yan; Xu, Chong-Rui; Yan, Li-Xu; Li, Yu-Fa; Zhong, Wen-Zhao; et al.
ABSTRACT: Patients with EGFR mutations showed unfavorable response to programmed cell death-1 (PD-1) blockade immunotherapy in non-small cell lung cancer (NSCLC). Yet the underlying association between EGFR mutation and immune resistance remains largely unclear. We performed an integrated analysis of PD-ligand 1(PD-L1)/CD8 expression and mutation profile based on the repository database and resected early-stage NSCLC in Guangdong Lung Cancer Institute (GLCI). Meanwhile, 2 pool-analyses were set to clarify the correlation between EGFR mutation and PD-L1 expression, and the association of EGFR status with response to anti-PD-1/L1 therapy. Pool-analysis of 15 public studies suggested that patients with EGFR mutations had decreased PD-L1 expression (odds ratio: 1.79, 95% CI: 1.10–2.93; P = 0.02). Analysis of The Cancer Genome Atlas (TCGA) and the GCLI cohort confirmed the inverse correlation between EGFR mutation and PD-L1 expression. Furthermore, patients with EGFR mutation showed a lack of T-cell infiltration and shrinking proportion of PD-L1 + /CD8 + TIL (P = 0.034). Importantly, patients with EGFR mutations, especially the sensitive subtype, showed a significantly decreased mutation burden, based on analysis of the discovery and validation sets. Finally, a pool-analysis of 4 randomized control trials confirmed that patients with EGFR mutation did not benefit from PD-1/L1 inhibitors (Hazard ratio [HR] = 1.09, P = 0.51) while patients with EGFR wild-type did (HR = 0.73, P < 0.00001). This study provided evidence of a correlation between EGFR mutations and an uninflamed tumor microenvironment with immunological tolerance and weak immunogenicity, which caused an inferior response to PD-1 blockade in NSCLCs.